Clinical usefulness of red dichromatic imaging in hemostatic treatment during endoscopic submucosal dissection: First report from a multicenter, open‐label, randomized controlled trial. Issue 2 (20th December 2021) - Fujimoto, Ai; Saito, Yutaka; Abe, Seiichiro; Hoteya, Syu; Nomura, Kosuke; Yasuda, Hiroshi; Matsuo, Yasumasa; Uraoka, Toshio; Kuribayashi, Shiko; Tsuji, Yosuke; Ohki, Daisuke; Maehata, Tadateru; et al.
Abstract : Objectives: To verify the efficacy and safety of red dichromatic imaging (RDI) in hemostatic procedures during endoscopic submucosal dissection (ESD). Methods: This is a multicenter randomized controlled trial of 404 patients who underwent ESD of the esophagus, stomach, colorectum. Patients who received hemostatic treatments by RDI during ESD were defined as the RDI group ( n  = 204), and those who received hemostatic treatments by white light imaging (WLI) were defined as the WLI group ( n  = 200). The primary endpoint was a shortening of the hemostasis time. The secondary endpoints were a reduction of the psychological stress experienced by the endoscopist during the hemostatic treatment, a shortened treatment time, and a non‐inferior perforation rate, in RDI versus WLI. Results: The mean hemostasis time in RDI ( n  = 860) was not significantly shorter than that in WLI ( n  = 1049) (62.3 ± 108.1 vs. 56.2 ± 74.6 s; P  = 0.921). The median hemostasis time was significantly longer in RDI than in WLI (36.0 [18.0–71.0] vs. 28.0 [14.0–66.0] s; P  = 0.001) in a sensitivity analysis. The psychological stress was significantly lower in RDI than in WLI (1.71 ± 0.935 vs. 2.03 ± 1.038; P  < 0.001). There was no significant difference in the ESD treatment time between RDI ( n  = 161) and WLI ( n  = 168) (58.0 [35.0–86.0] vs. 60.0 [38.0–88.5] min; P  = 0.855). Four perforations were observed, but none of them took place during the hemostatic treatment. Conclusions: Hemostatic treatment using RDI does not shorten the hemostasis time. RDI, however, is safe to use for hemostatic procedures and reduces the psychological stress experienced by endoscopists when they perform hemostatic treatment during ESD. UMIN000025134.